Cross-Checking: A Method to Test the Comprehensiveness of Pigot's Nineteenth-Century Plans of Manchester & Salford. (3rd April 2017) - Robson, Brian
Abstract : The long sequence of Pigot's plans of Manchester and Salford is used to test the concept that the dates of churches and chapels can be used as a valuable indicator of the completeness of the coverage of large-scale nineteenth-century town plans. The approach appears to hold some promise and suggests that Pigot's plans were surprisingly comprehensive. This may reflect not merely his drawing on existing surveys but, more interestingly, may be the incidental product of collecting data for his town directories. The methodology could usefully be extended to explore the value of directory plans of other towns.